Promoting Good Corporate Governance Principles in the Banking Industry: Exploration of the Role of the Banking Supervisor - Javed, Afshan Genevieve (2006)
In this paper I explore the topic of corporate governance applied to the banking industry and within it, the role of the Banking Supervisor. The topic of corporate governance has been gaining popularity since the 1990s as a necessary objective for all listed companies. Furthermore, this topic has been of great prominence and public interest because of the lack of sound corporate governance practices in some major companies across the world have showed- most of these corporate scandals of recent years have been linked to corporate governance practices. Most of the documentation which exists on the topic of corporate governance and supervision is theoretical. The goal of this research is to bring practical insight to a recent issue in the most regulated industry, after meeting with professionals in that domain. The banking industry is facing quite a dilemma: on one hand it is an ever growing business competing for more clients, more shareholders and market domination, but on the other hand it has found itself needing to comply to stricter corporate governance regulations, which can be seen as limiting its short-term competitiveness but ironically, ensure its long-term survival. Good corporate governance practices also guarantee a stronger financial system hence economic stability. The Banking Supervisor's role is essential to promote sound practice of corporate governance, by making sure that banks' structure is appropriate and adequate to permit the application of national banking standards at the institutional level and new international requirements such as the Basel II Capital Accord. Although the Banking Supervisor can be seen most visibly in its enforcement and disciplinary role, it has to have many more additional qualities: that of monitor, adviser, communication link and ultimately the guardian and protector of the financial markets.